Is nurse-led telephone follow-up for post-operative obstructive sleep apnoea patients effective? A prospective observational study at a paediatric tertiary centre. (February 2020) - Walijee, Hussein; Sood, Salil; Markey, Anne; Krishnan, Madhankumar; Lee, Anita; De, Sujata
Abstract: Objectives: To assess the effectiveness and patient satisfaction of a nurse-led telephone follow-up service in children following surgery for sleep disordered breathing (SDB)/obstructive sleep apnoea (OSA) in a tertiary paediatric hospital. Design: Prospective observational uncontrolled study. Participants: Children under the age of 16 undergoing adenoid and/or tonsil surgery between June 2015 and June 2018 for SDB or OSA. Parents were contacted by telephone six weeks post-operatively by an ENT nurse specialist. The T-14 questionnaire was utilised to assess post-operative outcomes. Parents were subsequently asked to evaluate their experience of this nurse-led telephone consultation service between June 2016 and April 2017. Results: 535 patients were included with an average post-operative T-14 score of 2.13 (95% CI 1.7–2.5). 430 patients were discharged following the nurse-led telephone consultation with a mean post-operative T-14 score 1.0 (95% CI 0.8–1.2). 105 patients were subsequently reviewed in clinic with an average T-14 score of 6.88 (95% CI 5.25–8.51). 36 (6.7%) patients had ongoing symptoms of SDB or OSA. 55 parents were invited to provide an evaluation of the nurse-led telephone FU clinic, which showed a 100% satisfaction rate with the service. Conclusion: A nurse-led telephone follow-up service is efficient and safe with high levels of parental satisfaction. It reduces unnecessary follow-up of uncomplicated patients whilst providing a robust safety net for those with ongoing problems. Highlights: Nurse-led follow up is a well-established phenomenon in many other specialities. This study provides insight into the safety and effectiveness of nurse-led telephone consultations. All patients surveyed were fully satisfied with the nurse-led telephone follow-up service.